Organizing for instruction in education systems and school organizations: How the subject matters - Spillane, James P; Hopkins, Megan (Journal of curriculum studies, 2013)
Teaching, the core technology of schooling, is an essential consideration in investigations of education systems and school organizations. Taking teaching seriously as an explanatory variable in research on education systems and organizations necessitates moving beyond treating it as a unitary practice, so as to take account of the school subjects implicated in the work. Building on and extending earlier work, in this paper we examine subject matter differences in how one education system (Local Educational Agency) and its elementary schools organize for instruction in the core elementary school subjects. Specifically, this paper explores how education leaders and teachers in one local American school district interact with one another with respect to advice and information about teaching and learning in literacy, mathematics and science. We examine similarities and differences in school staff members' advice and information networks and consider how these differences relate to the formal organizational infrastructure intended to support instruction.